Interessengetriebene audiovisuelle Szenenexploration - Kühn, Benjamin (Karlsruher Schriften zur Anthropomatik / Lehrstuhl für Interaktive Echtzeitsysteme, Karlsruher Institut für Technologie ; Fraunhofer-Inst. für Optronik, Systemtechnik und Bildauswertung IOSB Karlsruhe, 2016)
An ever-increasing integration of technology in our daily life took place over the last years. Humanoid robots like other autonomous systems are becoming increasingly relevant. For these systems it is essential to perceive their current environment at the required level of detail. Therefore, this publication introduces the interest-driven audiovisual scene exploration based on multimodal saliency, knowledge-driven curiosity and other aspects, which achieve an important scientific contribution.